STUDENTS' LEARNING MOTIVATION IN ONLINE LEARNING USING GOOGLE CLASSROOM AT SMKN 7 BALEENDAH - Wiranegara, Mohammad Rizky; Komaro, Mumu; Permana, Tatang (Universitas Pendidikan Indonesia, 2021)
This study aims to determine the learning motivation of students in online learning using Google Classroom in the subject of Basic Automotive Engineering (PDTO). The research method used is descriptive quantitative with ex post facto design. The research instrument used a validation questionnaire, a learning motivation questionnaire, and documentation. The research sample was students of class X TKRO 1 at SMKN 7 Baleendah. Determination of the sample by means of purposive sampling technique. The results showed that students' learning motivation was motivated by 72% and learning outcomes were below the KKM (75) with an average score of 54. The conclusion of this study is that learning motivation alone is not enough to get good learning outcomes. There are other factors that can influence, such as the way students absorb knowledge and how to organize and process the information or knowledge they acquire.